Phylogeny of Chinese Allium Species in Section Daghestanica and Adaptive Evolution of Allium (Amaryllidaceae, Allioideae) Species Revealed by the Chloroplast Complete Genome - Xie, Deng-Feng; Yu, Huan-Xi; Price, Megan; Xie, Chuan; Deng, Yi-Qi; Chen, Jun-Pei; Yu, Yan; Zhou, Song-Dong; He, Xing-Jin (Frontiers in Plant Science, 2019)
The genus Allium (Amaryllidaceae, Allioideae) is one of the largest monocotyledonous genera and it includes many economically important crops that are cultivated for consumption or medicinal uses. Recent advances in molecular phylogenetics have revolutionized our understanding of Allium taxonomy and evolution. However, the phylogenetic relationships in some Allium sections (such as the Allium section Daghestanica) and the genetic bases of adaptative evolution, remain poorly understood. Here, we newly assembled six chloroplast genomes from Chinese endemic species in Allium section Daghestanica and by combining these genomes with another 35 allied species, we performed a series of analyses including genome structure, GC content, species pairwise Ka/Ks ratios, and the SSR component, nucleotide diversity and codon usage. Positively selected genes (PSGs) were detected in the Allium lineage using the branch-site model. Comparison analysis of Bayesian and ML phylogeny on CCG (complete chloroplast genome), SCG (single copy genes) and CDS (conding DNA sequences) produced a well-resolved phylogeny of Allioideae plastid lineages, which illustrated several novel relationships with the section Daghestanica. In addition, six species in section Daghestanica showed highly conserved structures. The GC content and the GC3s content in Allioideae species exhibited lower values than studied non-Allioideae species, along with elevated pairwise Ka/Ks ratios. The rps2 gene was lost in all examined Allioideae species, and ten genes with significant posterior probabilities for codon sites were identified in the positive selection analysis, seven of them are associated with photosynthesis. Our study uncovered a new species relationship in section Daghestanica and suggested that the selective pressure has played an important role in Allium adaptation and evolution, these results will facilitate our further understanding of evolution and adaptation of species in the genus Allium.